2010
DOI: 10.1007/s10620-010-1500-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bowel Preparation with Polyethylene Glycol on Quality of Capsule Endoscopy

Abstract: Bowel preparation with PEG resulted in better image quality than fasting alone. No significant difference was observed between 2 and 4 l. PEG 2 l rather than 4 l may be a useful method of preparation for CE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 20 publications
0
59
0
Order By: Relevance
“…Various purgative and pro-kinetic bowel preparations have been studied to establish the ideal small bowel preparation method to maximize the diagnostic yield of VCE. Several early studies have supported the use of a purgative bowel cleanse prior to VCE [9,10,20,21]. On the contrary, a growing body of evidence suggests that a clear liquids bowel regimen prior to VCE produces equivalent image quality results and is better tolerated by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various purgative and pro-kinetic bowel preparations have been studied to establish the ideal small bowel preparation method to maximize the diagnostic yield of VCE. Several early studies have supported the use of a purgative bowel cleanse prior to VCE [9,10,20,21]. On the contrary, a growing body of evidence suggests that a clear liquids bowel regimen prior to VCE produces equivalent image quality results and is better tolerated by patients.…”
Section: Discussionmentioning
confidence: 99%
“…PEG solutions are non-absorbable and osmotically active and have been widely used in capsule endoscopy based on its ability to move through the bowel and potentially distend the lumen, wash out debris and bile, and possibly enhance small bowel transit time. The optimal dose of PEG that needs to be administered before SBCE is not entirely clear but 2 L appears to be sufficient [21][22][23] . A recent study concluded that the ingestion of a small amount of PEG after the swallowing of an endoscopy capsule significantly improved CE image quality, but did not enhance the completion rate to the cecum [24] .…”
Section: C B Amentioning
confidence: 99%
“…The amount of polyethylene glycol to be used has also been studied. Two liters of PEG has been found to be superior to none at all, but four liters of PEG has not been found to be of any further benefit [11,12].…”
Section: Preparation and Administrationmentioning
confidence: 93%
“…Results have been mixed. Purgatives appear to be of likely benefit [10][11][12]. Simethicone has been found to decrease intraluminal air bubbles and improve mucosal visibility, [79,80] but has also been shown to be inferior to magnesium citrate in grading of mucosal visibility [81].…”
Section: Poor Visualizationmentioning
confidence: 99%